ANÁLISIS DE LA PERCEPCIÓN DE LOS COLABORADORES PARA DETERMINAR SU NIVEL DE COMPROMISO (ENGAGEMENT) CON LA ORGANIZACIÓN O CON SU LÍDER - Reynoso-Núñez, Carlos; Ciófalo-Lagos, María Eugenia; González-Pérez, Manuel (European Scientific Journal, ESJ, 2015)
The purpose of this paper is to investigate why the staff of a company experiences commitment (engagement) in their work. We investigated whether this undertaking was due to the guidance of the leader or the prestige of the organization. This inquiry is validated statistically sufficient resources. Therefore, the questionnaire used for this study can be replicated by other researchers or professionals in the field. The results allow an approximation to reality from which the necessary identity can be addressed to the engagement. The reality mentioned is the perceived collaborator regarding the organization and the leader. These results indicate a stronger commitment to the organization workers (42.56%) than workers to the leader (21%).